Nanometer composite high-modulus agent, high-modulus asphalt concrete and preparation method of high-modulus asphalt concrete

Through the use of nanocomposite high-modulus agents, the problem that existing anti-rutting agents and high-modulus agents cannot meet the needs of high-grade highways and special heavy-duty sections has been solved, and the dynamic modulus and fatigue resistance of asphalt concrete have been significantly improved. Enhanced crack and rut resistance at low and high temperatures.

CN119118562APending Publication Date: 2024-12-13HUZHOU JIAOKE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411213786.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing anti-rutting agents and high-modulus agents cannot meet the use requirements of high-grade highways and special heavy-load sections, especially under high temperature and ultraviolet rays, which cannot effectively prevent early damage.

Method used

Using nanocomposite high modulus agents, including polyolefins, modified rubber powders, nanomodifiers, thermoplastic elastomers, synergistic crosslinkers, resin binders, antioxidants, polymer waxes and carbon black, through specific Formulation ratio and preparation method, nanocrosslinking points are formed to improve the dynamic modulus and fatigue resistance of asphalt concrete.

Benefits of technology

The dynamic modulus, dynamic stability and fatigue resistance of asphalt concrete are significantly improved, low-temperature crack resistance and high-temperature rutting resistance are enhanced, and the needs of heavy-duty asphalt pavement and durable asphalt pavement are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118562A_ABST
    Figure CN119118562A_ABST
Patent Text Reader

Abstract

The invention provides a nano-composite high-modulus agent, high-modulus asphalt concrete, a preparation method of the nano-composite high-modulus agent and the high-modulus asphalt concrete and the asphalt concrete. Comprising the following components: 52% of polyethylene, 13% of polypropylene, 3.6% of natural rubber powder, 14.4% of butadiene styrene rubber powder, 3% of a nano-CaCO3 modifier, 8% of a thermoplastic elastomer styrene-butadiene-styrene block copolymer (SBS), 2% of a cross-linking agent dicumyl peroxide (DCP), 2% of an anti-aging agent, 2% of an anti-aging agent, and 2% of an anti-aging agent. The preparation method comprises the following steps: adding 2% of a bisphenol A type epoxy resin E-12 binder, 1% of a hindered phenol 1010 antioxidant, 1.5% of polyethylene wax and 1% of carbon black masterbatch) and a nano composite high-modulus agent during aggregate dry mixing, adding asphalt, and adding mineral powder to prepare the nano high-modulus asphalt concrete. A nano modification technology is introduced into preparation of a high-modulus agent, so that the novel nano composite high-modulus asphalt concrete is prepared, and the comprehensive pavement performance of the asphalt concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asphalt pavement modification materials, and in particular to a nano-composite high modulus agent and high modulus asphalt concrete and a preparation method thereof. Background Art

[0002] With rapid economic development, traffic loads are increasing, particularly with heavy and overloaded vehicles. Coupled with persistent high temperatures due to climate change, many traditional asphalt pavements are experiencing severe early-stage damage under these conditions, including high temperatures, high speeds, heavy loads, and heavy traffic. Rutting is one of the most serious types of damage. To prevent early rutting and other asphalt pavement defects, new road materials are rapidly being developed. High-modulus asphalt concrete, with its excellent rutting and fatigue resistance, has attracted widespread attention within the industry.

[0003] The technology and concept of high-modulus asphalt concrete originated in France in the 1980s. By adding high-modulus agents to asphalt mixtures, the dynamic modulus and fatigue resistance of the asphalt mixture were increased, thereby improving the high-temperature deformation resistance of the entire asphalt pavement surface layer. In the early 21st century, high-modulus technology and concepts were introduced to countries such as the United Kingdom, Italy, Portugal, the United States, and China, and high-modulus asphalt concrete technology was further applied and developed. The research and application of high-modulus asphalt concrete in China started relatively late. One of the important indicators for asphalt pavement design in the "Highway Asphalt Pavement Design Code" (JTGE50-2017), promulgated in 2017, is an important evaluation index for the mechanical properties of high-modulus asphalt concrete.

[0004] Currently, the most effective methods for increasing the high-temperature modulus of asphalt concrete include using low-grade asphalt, natural asphalt, and adding high-modulus agents. Adding high-modulus agents is the most effective in increasing the dynamic modulus of asphalt concrete, and compared to technologies such as SBS-modified asphalt concrete, it offers better resistance to early rutting.

[0005] However, as the traffic volume increases, vehicle loads become heavier, and climate change continues to cause high temperatures, the current anti-rutting agents and high modulus agents cannot meet the requirements for use on high-grade highways and special heavy-load sections. In particular, asphalt will age under high temperatures and ultraviolet rays. The existing anti-rutting agents and high modulus agents can no longer meet the needs of asphalt pavement development. Summary of the Invention

[0006] In response to the problems pointed out in the background technology, the present invention proposes a nano-composite high modulus agent and a high modulus asphalt concrete and a preparation method thereof to solve the above technical problems.

[0007] The technical solution of the present invention is achieved as follows:

[0008] A nano composite high modulus agent comprises the following components: polyolefin, modified rubber powder, nano modifier, thermoplastic elastomer, synergistic cross-linking agent, resin binder, antioxidant, polymer wax and carbon black.

[0009] The present invention is further configured as follows: the polyolefin is a mixture of polyethylene (PE) and polypropylene (PP); the modified rubber powder is a mixture of natural rubber and styrene-butadiene rubber; the nano-modifier is a mixture of one or more of nano-CaCO3 and nano-SiO2; the thermoplastic elastomer is a thermoplastic polyolefin block copolymer, and the polyolefin block copolymer is a mixture of one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), and ethylene-vinyl acetate copolymer (EVA); the synergistic crosslinking agent is a mixture of one or more of the organic peroxide external crosslinking agent diisopropylbenzene peroxide DCP and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane; the resin adhesive is a mixture of one or more of bisphenol A epoxy resin E-12 and polyurethane (PU); the antioxidant is hindered phenol 1010; the polymer wax is polyethylene wax; and the carbon black is carbon black masterbatch.

[0010] The present invention is further configured to include the following ingredient formula ratios: 50-70% polyolefin, 10-20% modified rubber powder, 2-8% nano-modifier, 20-35% thermoplastic elastomer, 1-3% synergistic cross-linking agent, 3-10% resin binder, 0.5-2% antioxidant, 1-3% polymer wax, and 0.5-2% carbon black masterbatch; the mass ratio of polyethylene to polypropylene in the polyolefin is 4:1; the mass ratio of natural rubber to styrene-butadiene rubber in the modified rubber powder is 1:4.

[0011] A method for preparing a nanocomposite high modulus agent comprises the following steps:

[0012] Step (1), feeding polyolefin, modified rubber powder, nano-modifier and synergistic cross-linking agent into a high-pressure mixer in proportion and mixing them uniformly;

[0013] Step (2), feeding into a screw granulator, plasticizing and melting at 130-180°C, and forming and granulating to obtain rubber and plastic raw material A;

[0014] Step (3), adding the rubber and plastic raw material A, thermoplastic elastomer, synergistic crosslinking agent, resin binder, antioxidant, polymer wax, nano modifier, and carbon black masterbatch prepared in step (2) into a high-pressure mixer in proportion and mixing;

[0015] After step (4), the mixture is fed into a screw granulator, plasticized and melted at 150-190° C., and granulated to obtain a nano-composite high modulus agent, the melt mass flow rate (190° C., 21.6N) of which is ≥12 g / 10 min and the softening point is 130-150° C.

[0016] A nano-composite high modulus agent is prepared by firstly preparing a rubber-plastic particle masterbatch A by nano-modification of polyolefin and modified rubber powder, and then fusing and granulating the masterbatch A with a thermoplastic elastomer, a synergistic cross-linking agent, a resin binder, an antioxidant, a polymer wax, a nano-modifier, and a carbon black masterbatch to prepare a nano-composite high modulus modifier.

[0017] The present invention is further configured such that the nanocomposite high modulus modifier obtained in step (4) contains 2-8 g of nano modifier in 100 g of the nanocomposite high modulus modifier.

[0018] The present invention is further configured such that the proportion of the nano-modifier added twice in step (1) and step (3) is 50% of the total amount respectively.

[0019] The present invention is further configured such that the nanocomposite high modulus agent obtained in step (4) has an optimal dosage of 0.2-0.8% of the mass of the asphalt mixture.

[0020] The present invention is further configured such that the nanocomposite high modulus agent obtained in step (4) has a melt mass flow rate (190°C, 21.6N) ≥ 12g / 10min and a softening point of 130-150°C.

[0021] The present invention is further configured such that the nanocomposite high modulus agent obtained in step (4), when mixed with low-grade road petroleum asphalt used in actual engineering applications at an optimal dosage of 0.2-0.8%, produces an asphalt concrete binder having a softening point increase of ≥10°C and an elongation (25°C) of ≥10cm.

[0022] A nanocomposite high-modulus asphalt concrete with a medium-grained gradation includes the following components: coarse aggregate, fine aggregate, mineral powder, asphalt, and a nanocomposite high-modulus agent. The nanocomposite high-modulus agent is added during dry mixing of the aggregate at 180°C. The nanocomposite high-modulus agent is evenly dispersed throughout the aggregate through shearing action. After dry mixing with the aggregate for 60 seconds, the asphalt is added. Mixing continues for another 60 seconds, followed by the mineral powder, and then mixing for another 60 seconds, for a total mixing time of 180 seconds. This produces the nanocomposite high-modulus asphalt concrete. The nanocomposite high-modulus agent is added in an amount of 0.2-0.8% of the aggregate mass. The prepared nanocomposite high-modulus asphalt concrete exhibits a dynamic modulus (20°C, 10Hz) ≥18,000 MPa, a dynamic stability (60°C, 0.7MPa) ≥12,000 times / mm, and a low-temperature flexural failure strain (-10°C, 50mm / min) ≥2,600 με.

[0023] By adopting the above technical solution, the beneficial effects of the present invention are:

[0024] The nano-composite high modulus agent and high modulus asphalt concrete provided by the present invention and their preparation method are as follows: first, polyolefin, rubber powder and nano-modifier are nano-modified at 130-180°C to obtain a rubber-plastic masterbatch; then, the rubber-plastic masterbatch is plasticized and melted with a thermoplastic elastomer, a synergistic cross-linking agent, a resin binder, an antioxidant, a polymer wax, a nano-modifier and a carbon black masterbatch at 150-190°C, and granulated to obtain a nano-composite high modulus agent; finally, the nano-composite high modulus agent is directly added to the hot aggregate in the mixing equipment during dry mixing, and the shear force of the aggregate uniformly disperses the specially formulated modifier in the asphalt mixture, thereby obtaining nano-high modulus asphalt concrete.

[0025] The nanoparticles contained in the nanocomposite high modulus agent form nano-crosslinks that absorb energy, effectively improving the rheological properties, dimensional stability, and thermal stability of asphalt. They provide filling, reinforcement, and toughening, enhancing resistance to external damage, increasing toughness, and improving asphalt's flexibility and low-temperature crack resistance. The nano-activated calcium carbonate has a lipophilic and hydrophobic surface and good compatibility with resins, effectively improving or modulating asphalt's rigidity, toughness, and flexural strength, enhancing its low-temperature resistance and high-temperature rutting resistance.

[0026] When asphalt is mixed with heated aggregate, the nanocomposite high modulus agent melts at high temperature and adheres to the heated aggregate under the shearing action of the hot aggregate, forming a submicron fiber network (SFNs) structure, which restricts the sliding of the mineral aggregate, thereby modifying the surface of the aggregate, enhancing the interaction between the aggregates, and increasing the fatigue resistance, low-temperature frost cracking resistance and high-temperature stability of asphalt concrete.

[0027] The thermoplastic polymer in the nanocomposite high modulus agent melts at high temperatures and adheres to the heated aggregate. When the modified rubber powder is released from the coating, it is thoroughly mixed and fused with the asphalt. Dispersed in the asphalt mixture, the modified rubber powder forms physical crosslinks with the asphalt and absorbs the light oil components in the asphalt, raising the asphalt's softening point and thus improving the asphalt mixture's rutting resistance. Furthermore, it maintains flexibility even below its brittle point, increasing its toughness and improving the low-temperature performance of asphalt concrete.

[0028] The addition amount of nano-composite high modulus agent is 0.2-0.8% of the mass of asphalt concrete. The prepared nano-high modulus asphalt concrete, graded AC-20 test block, 80mm thick test piece is kept warm for 6 hours, and under the conditions of 60℃±0.5℃, 0.7MPa, the rutting tester is started, and the test wheel is made to travel back and forth for 12 hours. After testing, the dynamic stability (60℃, 0.7MPa) is ≥12000 times / mm, the low-temperature bending failure strain (-10℃, 50mm / min) is ≥2600με, and the dynamic modulus (20℃, 10Hz) is ≥18000MPa.

[0029] This application introduces nano-modification technology into the preparation of high modulus agents, thereby preparing a new type of nano-composite high modulus asphalt concrete, so as to improve the comprehensive road performance of asphalt concrete and meet the needs of heavy-load asphalt pavement and durable asphalt pavement construction.

[0030] Asphalt concrete, commonly known as asphalt concrete, is a mixture of artificially selected mineral materials with a certain graded composition, such as crushed stone or crushed gravel, stone chips or sand, mineral powder, etc., and a certain proportion of road asphalt materials, mixed under strictly controlled conditions. Asphalt concrete is mainly used in asphalt pavements.

[0031] In order to improve the comprehensive road performance of asphalt pavement, nano-composite high modulus agent is added to asphalt concrete to improve the asphalt pavement's ability to resist permanent deformation, fatigue, high-temperature rutting, low-temperature cracking, water damage and other diseases. The nano-active calcium carbonate and nano-active silica in this application have lipophilic and hydrophobic surfaces and good compatibility with resins. They can effectively improve or adjust the rigidity, toughness and bending strength of asphalt; and can effectively improve the rheological properties, dimensional stability and heat stability of asphalt, and have the functions of filling, reinforcing and toughening, so that its cold resistance and rutting resistance are enhanced. The prepared nano-composite high modulus agent is added to asphalt concrete, and the prepared nano-composite high modulus asphalt concrete can significantly improve the dynamic modulus, dynamic stability and fatigue resistance of asphalt mixed concrete after repeated tests.

[0032] The core invention of this application is the application of nano-modification technology to the preparation of nano-composite high-modulus agents. This agent is then used to further prepare high-modulus concrete. Advantages: The nanoparticles contained in the nano-composite high-modulus agent form nano-crosslinking points that absorb energy, effectively improving the rheological properties, dimensional stability, and thermal stability of asphalt. It also has filling, reinforcing, and toughening effects, enhancing resistance to external damage, increasing toughness, improving the flexibility of asphalt, and enhancing low-temperature crack resistance. Compared with the use of conventional high-modulus agents, the low-temperature crack resistance, high-temperature stability, and fatigue resistance of nano-composite high-modulus asphalt concrete are significantly improved.

[0033] After investigation, no prior research has been found to apply nanotechnology to the preparation of high-modulus asphalt modifiers. The nanocomposite high-modulus modification technology is also the innovation of this application. While nanotechnology has been gradually applied in other fields, its application in the field of asphalt modifiers is a first, and holds significant significance for the development of transportation construction and asphalt pavement in my country. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0035] Figure 1 This is a comparison chart of the rutting test results for the nanocomposite high-modulus asphalt concrete of the present invention. The test conditions were as follows: The rutting tester was maintained at 60°C ± 0.5°C, 0.7 MPa, and the AC-20 graded, 80mm thick specimens were kept warm for 6 hours. The rutting deformation automatic recorder was then activated, and the testing machine was then started. The test wheels were driven back and forth for 48 hours, and the rutting patterns of the specimens were compared.

[0036] Figure 2 These are SEM images of the cross section of asphalt concrete containing nano-composite high modulus agent, a SEM image containing nano-high modulus agent, b SEM image without nano-high modulus agent. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0038] The present invention is described as follows:

[0039] Example 1:

[0040] A nano-composite high modulus agent comprises the following components: 52% polyethylene, 13% polypropylene, 3.6% natural rubber powder, 14.4% styrene-butadiene rubber powder, 3% nano-CaCO3 modifier, 8% thermoplastic elastomer styrene-butadiene-styrene block copolymer (SBS), 2% cross-linking agent dicumyl peroxide DCP, 2% bisphenol A type epoxy resin E-12 binder, 1% hindered phenol 1010 antioxidant, 1.5% polyethylene wax, and 1% carbon black masterbatch.

[0041] Functions of each component:

[0042] Polyethylene: As one of the main components, polyethylene has good chemical stability, corrosion resistance and mechanical properties. It provides the basic strength and toughness of the modifier.

[0043] Polypropylene: Increases the hardness and rigidity of the material while also improving heat resistance and chemical stability.

[0044] Natural rubber powder and styrene-butadiene rubber powder: provide elasticity and flexibility, and improve the impact resistance of the material.

[0045] Nano-CaCO3 modifier: Nano-scale calcium carbonate can increase the modulus and strength of the material, while also improving the processing performance and heat resistance of the material.

[0046] Thermoplastic elastomer SBS: gives the material good elasticity and processability, and also improves the material's low-temperature resistance.

[0047] Cross-linking agent dicumyl peroxide DCP: promotes the cross-linking reaction of the material and improves the strength and heat resistance of the material.

[0048] Bisphenol A epoxy resin E-12 adhesive: enhances the bonding strength between components and improves the integrity and stability of the material.

[0049] Hindered phenol 1010 antioxidant: prevents the material from being oxidized during processing and use, extending the service life of the material.

[0050] Polyethylene wax: plays a role in lubrication and dispersion, improving the processing performance of the material.

[0051] Carbon black masterbatch: gives the material a certain color, and also improves the material's weather resistance and UV resistance.

[0052] Performance characteristics:

[0053] High modulus: Due to the effects of components such as nano-CaCO3 modifier, this modifier has a higher modulus and can improve the strength and rigidity of the material.

[0054] Good elasticity and toughness: The presence of natural rubber powder, styrene-butadiene rubber powder and thermoplastic elastomer SBS gives the material good elasticity and toughness, and the ability to withstand certain impact and deformation.

[0055] Heat resistance and chemical corrosion resistance: Polyethylene, polypropylene and other components have good heat resistance and chemical corrosion resistance. Combined with the effect of antioxidants, the modifier can maintain stable performance even in high temperature and harsh environments.

[0056] Processability: The addition of components such as polyethylene wax improves the processing properties of the material, making it easy to process and shape.

[0057] Good adhesion: Bisphenol A epoxy resin E-12 adhesive enhances the adhesion between the components, enabling the modifier to combine well with other materials.

[0058] A method for preparing a nanocomposite high modulus agent comprises the following steps:

[0059] Step (1): polyethylene, polypropylene, natural rubber powder, styrene-butadiene rubber powder, nano-CaCO3 modifier, and synergistic crosslinking agent dicumyl peroxide (DCP) are sequentially fed into a high-speed mixer and mixed uniformly. Polyethylene, polypropylene, natural rubber powder, styrene-butadiene rubber powder, nano-CaCO3 modifier, and synergistic crosslinking agent dicumyl peroxide (DCP) are prepared in proportion and fed into a high-speed mixer to mix these raw materials. The high-speed mixer can fully mix the different raw materials and ensure that the components can work synergistically in the subsequent processing. In this step, the amount of nano-modifier and synergistic crosslinking agent added is half of their total amount.

[0060] Step (2), feeding the mixture of the above step (1) into a screw granulator, plasticizing and melting at 130-180°C, and forming and granulating to obtain rubber-plastic masterbatch A. Feed the mixture uniformly mixed in step (1) into a screw granulator. The screw granulator plasticizes and melts the mixture at a temperature of 130-180°C by heating and extrusion. In this process, the mixture gradually becomes a molten state, which is convenient for forming and granulating. In the plasticized and molten state, the mixture is formed and granulated through a specific mold to obtain rubber-plastic masterbatch A. The forming and granulation process determines the particle size and shape of the masterbatch, which is very important for subsequent processing and use. Appropriate particle size and shape can improve processing efficiency and ensure product quality stability.

[0061] Step (3) adds the rubber and plastic raw material A prepared in step (2), the thermoplastic elastomer styrene-butadiene-styrene block copolymer (SBS), the synergistic crosslinking agent diisopropylbenzene peroxide DCP, the bisphenol A type epoxy resin E-12 binder, the hindered phenol 1010 antioxidant, the polyethylene wax, the nano-CaCO3 modifier, and the carbon black masterbatch to a high-speed mixer in proportion and mixes them evenly. In the high-speed mixer, these raw materials are fully mixed evenly. The purpose of this step is to ensure that the components can be evenly distributed during the subsequent processing process and improve the performance stability of the product.

[0062] Step (4): feeding the mixture of step (3) into a screw granulator, and plasticizing and melting the mixture again at a temperature of 150-190° C., and forming and granulating to obtain a nanocomposite high modulus agent, the melt mass flow rate of the product (190° C., 21.6 N) being ≥12 g / 10 min, and the softening point being 130-150° C.

[0063] In the nanocomposite high modulus agent obtained in step (4), 100 g of the nanocomposite high modulus agent contains 4 g of the nano modifier.

[0064] A nano-composite high-modulus asphalt concrete, AC-20 gradation includes the following components: coarse aggregate, fine aggregate, mineral powder, asphalt, and a nano-composite high-modulus modifier. The nano-composite high-modulus modifier is added at 180° C. during dry mixing of the aggregate, and is uniformly dispersed into the aggregate through the shearing action of the aggregate. After dry mixing with the aggregate for 60 seconds, asphalt is added, and after continuing to mix for 60 seconds, the mineral powder is added, and then mixed for another 60 seconds. The total mixing time is 180 seconds, thereby producing the nano-high-modulus asphalt concrete.

[0065] Coarse aggregate, fine aggregate and mineral powder: These are the main skeleton components of asphalt concrete, providing strength and stability. Coarse aggregate is usually larger particles of rock or gravel, while fine aggregate is smaller particles of sand, etc. Mineral powder can improve the adhesion between asphalt and aggregate. Asphalt: As a binder, it bonds aggregates together to form a solid whole. The performance of asphalt has an important influence on the durability, water resistance and crack resistance of asphalt concrete. Nano-composite high modulus agent: The addition of this modifier can significantly increase the modulus of asphalt concrete, giving it higher strength and stiffness. At the same time, nano-scale particles can improve the interfacial properties between asphalt and aggregate, and improve adhesion and durability.

[0066] Adding the nanocomposite high modulus agent during dry-mixing of aggregates: Add the nanocomposite high modulus agent to the aggregates and dry-mix at 180°C. This temperature allows the modifier to melt quickly, allowing for better contact with the aggregates and uniform dispersion. The strong shearing action of the aggregates helps evenly disperse the modifier throughout the aggregate, ensuring its full effectiveness during subsequent mixing. Adding asphalt and continuing mixing: After dry-mixing with the aggregates for 60 seconds, add the asphalt. The addition of asphalt strengthens the bond between the aggregates and interacts with the nanocomposite high modulus agent, further improving the performance of the asphalt concrete. Continuing to mix for 60 seconds ensures that the asphalt is thoroughly mixed with the aggregates and modifier. Adding mineral powder and then mixing: Next, add the mineral powder. The mineral powder fills the gaps between the aggregates, improving the density and stability of the asphalt concrete. Mix for another 60 seconds to evenly distribute the mineral powder throughout the asphalt concrete, ensuring overall uniformity of performance. The total mixing time is 180s: By controlling the total mixing time to 180s, it can be ensured that the various components are fully mixed to form a uniform and stable nano high modulus asphalt concrete.

[0067] It should be noted that these specific content ratios are not fixed, but will be appropriately adjusted in different gradings based on various factors such as the specific needs of the project, construction environment conditions, and the quality characteristics of the raw materials.

[0068] Table 1 Aggregate gradation range of nanocomposite high modulus asphalt concrete

[0069]

[0070] A nanocomposite high modulus asphalt concrete, graded AC-20 test piece, 80mm thick, was held at 60°C ± 0.5°C, 0.7MPa for 6 hours. A rutting deformation automatic recorder was started, followed by a rutting tester. The test wheels were driven back and forth for 12 hours. The test results are as follows:

[0071] Table 2 Performance indexes of asphalt concrete added with nanocomposite high modulus agent

[0072]

[0073] Example 2:

[0074] A nano-composite high modulus agent comprises the following components: 46.4% polyethylene, 11.6% polypropylene, 4% natural rubber powder, 16% styrene-butadiene rubber powder, 4.5% nano-SiO2 modifier, 6.5% thermoplastic elastomer ethylene-vinyl acetate copolymer (EVA), 2.5% synergistic crosslinking agent 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, 4% resin binder polyurethane (PU), 1.5% hindered phenol 1010 antioxidant, 2% polyethylene wax, and 1% carbon black masterbatch.

[0075] A method for preparing a nanocomposite high modulus agent comprises the following steps:

[0076] Step (1), polyethylene, polypropylene, natural rubber powder, styrene-butadiene rubber powder, nano-SiO2 modifier, and synergistic crosslinking agent 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane are sequentially fed into a high-pressure mixer and mixed uniformly.

[0077] Step (2): feeding the mixed material of the above step (1) into a screw granulator, plasticizing and melting at 130-180° C., and forming and granulating to obtain rubber-plastic masterbatch A.

[0078] Step (3), the rubber and plastic raw material A prepared in step (2), the thermoplastic elastomer ethylene-vinyl acetate copolymer (EVA), the synergistic crosslinking agent 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, the polyurethane (PU) binder, the hindered phenol 1010 antioxidant, the polyethylene wax, the nano-SiO2 modifier, and the carbon black masterbatch are added to a high-speed mixer in proportion and mixed.

[0079] Step (4), feeding the mixture of the above step (3) into a screw granulator, plasticizing and melting at 150-190°C, and forming and granulating to obtain a nano-composite high modulus agent, the melt mass flow rate (190°C, 21.6N) of which is ≥12g / 10min and the softening point is 130-150°C.

[0080] The present invention is further configured such that, in the nano-composite high modulus agent obtained in step (4), 100 g of the nano-composite high modulus agent contains 5 g of nano-SiO2 modifier.

[0081] A nano-composite high-modulus asphalt concrete, AC-20 gradation includes the following components: coarse aggregate, fine aggregate, mineral powder, asphalt, and a nano-composite high-modulus agent. The nano-composite high-modulus agent is added at 180° C. during dry mixing of aggregates, and is uniformly dispersed into the aggregates through the shearing action of the aggregates. After dry mixing with the aggregates for 60 seconds, asphalt is added, and after continuing to mix for 60 seconds, the mineral powder is added, and then mixing for another 60 seconds. The total mixing time is 180 seconds, thereby producing the nano-high-modulus asphalt concrete.

[0082] Table 3 Aggregate gradation range of nanocomposite high modulus asphalt concrete

[0083]

[0084] A nanocomposite high modulus asphalt concrete, graded AC-20 test piece, 80mm thick, was held at 60°C ± 0.5°C, 0.7MPa for 6 hours. A rutting deformation automatic recorder was started, followed by a rutting tester. The test wheels were driven back and forth for 12 hours. The test results are as follows:

[0085] Table 4 Performance indexes of asphalt concrete added with nanocomposite high modulus agent

[0086]

[0087] Example 3:

[0088] A nano-composite high modulus agent comprises the following components: 52.8% polyethylene, 13.2% polypropylene, 3% natural rubber powder, 12% styrene-butadiene rubber powder, 5% nano-CaCO3 modifier, 6% thermoplastic elastomer styrene-isoprene-styrene block copolymer (SIS), 2.5% cross-linking agent dicumyl peroxide DCP, 2% bisphenol A type epoxy resin E-12 binder, 1.5% hindered phenol 1010 antioxidant, 1% polyethylene wax, and 1% carbon black masterbatch.

[0089] A method for preparing a nanocomposite high modulus agent comprises the following steps:

[0090] Step (1), polyethylene, polypropylene, natural rubber powder, styrene-butadiene rubber powder, nano-CaCO3 modifier, and synergistic crosslinking agent dicumyl peroxide DCP are sequentially fed into a high-speed mixer and mixed evenly.

[0091] Step (2): feeding the mixed material of the above step (1) into a screw granulator, plasticizing and melting at 130-180° C., and forming and granulating to obtain rubber-plastic masterbatch A.

[0092] Step (3), the rubber and plastic raw material A prepared in step (2), the thermoplastic elastomer styrene-isoprene-styrene block copolymer (SIS), the crosslinking agent diisopropyl peroxide, the bisphenol A type epoxy resin E-12 binder, the hindered phenol 1010 antioxidant, the polyethylene wax, and the carbon black masterbatch are added to a high-speed mixer in proportion and mixed.

[0093] Step (4), feeding the mixture of the above step (3) into a screw granulator, plasticizing and melting at 150-190°C, and forming and granulating to obtain a nano-composite high modulus agent, the melt mass flow rate (190°C, 21.6N) of which is ≥12g / 10min and the softening point is 130-150°C.

[0094] The present invention is further configured such that, in the nano-composite high modulus agent obtained in step (4), 100 g of the nano-composite high modulus agent contains 5 g of the nano-modifier.

[0095] A nano-composite high-modulus asphalt concrete, AC-20 gradation includes the following components: coarse aggregate, fine aggregate, mineral powder, asphalt, and a nano-composite high-modulus agent. The nano-composite high-modulus agent is added at 180° C. during dry mixing of aggregates, and is uniformly dispersed into the aggregates through the shearing action of the aggregates. After dry mixing with the aggregates for 60 seconds, asphalt is added, and after continuing to mix for 60 seconds, the mineral powder is added, and then mixing for another 60 seconds. The total mixing time is 180 seconds, thereby producing the nano-high-modulus asphalt concrete.

[0096] Table 5 Aggregate gradation range of nanocomposite high modulus asphalt concrete

[0097]

[0098] A nanocomposite high modulus asphalt concrete, graded AC-20 test piece, 80mm thick, was held at 60°C ± 0.5°C, 0.7MPa for 6 hours. A rutting deformation automatic recorder was started, followed by a rutting tester. The test wheels were driven back and forth for 12 hours. The test results are as follows:

[0099] Table 6 Performance indexes of asphalt concrete added with nanocomposite high modulus agent

[0100]

[0101]

[0102] The core invention of the above technical solution lies in the composite modification of high modulus agents through nanotechnology, which effectively improves the rheological properties, dimensional stability and heat stability of asphalt, has the functions of filling, reinforcing and toughening, enhances the ability to resist external force damage, increases toughness, improves the flexibility of asphalt, enhances low-temperature crack resistance and high-temperature deformation resistance, thereby improving the modification effect of asphalt mixture.

[0103] It should be noted that the specific content ratio of mineral materials in these gradations is not fixed, but will be appropriately adjusted according to various factors such as the specific needs of the project, construction environment conditions, and quality characteristics of the raw materials.

[0104] The weight ratio of the nanocomposite high modulus agent to the asphalt mixture is (0.2-0.8):100. Due to the small amount of nanocomposite high modulus agent added, uneven dispersion of the nanocomposite high modulus agent within the asphalt mixture can ultimately lead to poor asphalt mixture modification. Therefore, the method of use of the present invention allows the nanocomposite high modulus agent to quickly melt and evenly disperse into the aggregate, thereby modifying the entire asphalt mixture and improving its overall road performance.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A nanocomposite high modulus agent, Features: The components include: Polyolefins, Modified rubber powder, Nano modifiers, Thermoplastic elastomers, Synergistic crosslinking agent, Resin binder, Antioxidants, Polymer wax, Carbon black.

2. A nanocomposite high modulus agent according to claim 1, Features: The polyolefin is a mixture of polyethylene (PE) and polypropylene (PP); The modified rubber powder is a mixture of natural rubber and styrene-butadiene rubber; The nano modifier is nano CaCO 3 and nano-SiO 2 One or more mixtures thereof; The thermoplastic elastomer is a thermoplastic polyolefin block copolymer, and the polyolefin block copolymer is a mixture of one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), and ethylene-vinyl acetate copolymer (EVA); The synergistic crosslinking agent is a mixture of one or more of an organic peroxide external crosslinking agent dicumyl peroxide DCP and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane; The resin adhesive is a mixture of one or more of bisphenol A epoxy resin E-12 and polyurethane (PU); The antioxidant is hindered phenol 1010; The polymer wax is polyethylene wax; The carbon black is carbon black masterbatch.

3. A nanocomposite high modulus agent according to claim 2, Features: The formula includes the following ingredients: Polyolefin 50-70%, Modified rubber powder 10-20%, Nano modifier 2-8%, Thermoplastic elastomer 20-35%, Synergistic cross-linking agent 1-3%, Resin binder 3-10%, Antioxidants 0.5-2%, Polymer wax 1-3%, Carbon black masterbatch 0.5-2%; The mass ratio of polyethylene to polypropylene in the polyolefin is 4:1; the mass ratio of natural rubber to styrene-butadiene rubber in the modified rubber powder is 1:

4.

4. A method for preparing a nanocomposite high modulus agent, Features: The steps include: Step (1), feeding polyolefin, modified rubber powder, nano-modifier, and synergistic cross-linking agent into a high-speed mixer in the proportions as described in claim 3 and mixing them uniformly; Step (2), feeding into a screw granulator, plasticizing and melting at 130-180°C, and forming and granulating to obtain rubber and plastic raw material A; Step (3), adding the rubber and plastic raw material A, thermoplastic elastomer, synergistic crosslinking agent, resin binder, antioxidant, polymer wax, nano modifier, and carbon black masterbatch prepared in step (2) into a high-speed mixer in proportion and mixing; Step (4), feeding into a screw granulator, plasticizing and melting at 150-190°C, forming and granulating to obtain a nano-composite high modulus agent, wherein the melt mass flow rate (190°C, 21.6N) is ≥12g / 10min, and the softening point is 130-150°C.

5. A method for preparing a nanocomposite high modulus agent according to claim 4, Features: The nanocomposite high modulus agent obtained in step (4) contains 2-8 g of nano modifier in 100 g of the nanocomposite high modulus agent.

6. A method for preparing a nanocomposite high modulus agent according to claim 4, Features The proportion of the nano-modifier added twice in step (1) and step (3) is 50% of the total amount respectively.

7. A method for preparing a nanocomposite high modulus agent according to claim 4, Features: The nanocomposite high modulus agent obtained in step (4) has an optimal dosage of 0.2-0.8% of the mass of the asphalt mixture.

8. A method for preparing a nanocomposite high modulus agent according to claim 4, Features: The nanocomposite high modulus agent obtained in step (4) has a melt mass flow rate (190° C., 21.6 N) ≥ 12 g / 10 min and a softening point of 130-150° C.

9. A method for preparing a nanocomposite high modulus agent according to claim 4, Features: The nanocomposite high modulus agent obtained in step (4), when mixed with low-grade road petroleum asphalt used in actual engineering applications, produces an asphalt concrete binder with an increase in softening point of ≥10°C and an elongation (25°C) of ≥10cm under the condition of an optimal dosage of 0.2-0.8%.

10. A nanocomposite high modulus asphalt concrete, Features: It includes coarse aggregate, fine aggregate, mineral powder, asphalt, and nano-composite high modulus agent. The nano-composite high modulus agent is added when the aggregate is dry mixed, and the addition amount of the nano-composite high modulus agent is 0.2-0.8% of the mass of the aggregate. The prepared nano-composite high modulus asphalt concrete has a dynamic modulus (20℃, 10Hz) ≥18000MPa, a dynamic stability (60℃, 0.7MPa) ≥12000 times / mm, and a low-temperature bending failure strain (-10℃, 50mm / min) ≥2600με.